Skin Interface, a Key Player for Borrelia Multiplication and Persistence in Lyme Borreliosis. Issue 3 (March 2020) - Bernard, Quentin; Grillon, Antoine; Lenormand, Cédric; Ehret-Sabatier, Laurence; Boulanger, Nathalie
Abstract : The skin plays a key role in vector-borne diseases because it is the site where the arthropod coinoculates pathogens and its saliva. Lyme borreliosis, particularly well investigated in this context, is a multisystemic infectious disease caused by Borrelia burgdorferi sensu lato and transmitted by the hard tick Ixodes . Numerous in vitro studies were conducted to better understand the role of specific skin cells and tick saliva in host defense, vector feeding, and pathogen transmission. The skin was also evidenced in various animal models as the site of bacterial multiplication and persistence. We present the achievements in this field as well as the gaps that impede comprehensive knowledge of the disease pathophysiology and the development of efficient diagnostic tools and vaccines in humans. Highlights: The skin is a key interface in vector-borne diseases, such as malaria, trypanosomiasis, leishmaniasis, and dengue fever, as a site of pathogen and vector saliva inoculation. The saliva of the Ixodes ticks plays a major role in the modulation of the pharmacology (coagulation, pain, and itching) and the immunology of the vertebrate host. Tick saliva is, together with that of the sandfly, among the best studied in arthropods. The skin is an important site of multiplication and persistence of Borrelia, the extracellular bacterium responsible for Lyme borreliosis. The persistence occurs in the absence of skin inflammation, which highlights the immunotolerance of the host skin to the bacteria. Investigation of the skin as an immunotolerant organ should be intensified to favor the identification of new vaccine candidates and to develop innovative diagnostic techniques such as proteomics.